Transgender Dalam Kacamata Hukum Waris, Studi Komparatif Antara Hukum Islam Dan Adat Minangkabau - Damanik, Wahda Hilwani; Muwafikka, Anna; Anggraini, Anggi Egi (Al-Muqaranah : Jurnal Perbandingan Hukum dan Mazhab, 2025)
Transgender individuals often face challenges in claiming inheritance rights due to legal and cultural perceptions of gender identity. This study aims to examine how Islamic law and Minangkabau customary law regulate inheritance rights for transgender people. The research uses normative and sociological approaches, analyzing legal texts and conducting interviews with religious and traditional leaders. In Islamic law, transgender individuals may be entitled to inheritance if their gender status is clearly recognized both legally and medically. On the other hand, Minangkabau customary law, which follows a matrilineal system, allows transgender individuals to inherit movable property (pusaka rendah) if they conform to female social roles, but denies them access to ancestral property (pusaka tinggi). The findings indicate that both legal systems still lack comprehensive protection and recognition for transgender individuals in matters of inheritance. Therefore, reinterpretation and reform are needed to ensure fair and inclusive inheritance rights that reflect the social realities of today. Keywords: transgender, inheritance law, Islamic law, Minangkabau